Relationship between Indebtedness and profitability in industrial manufacturing companies in Ecuador - Buele Nugra, Irene; Dominguez, Leonel; Alvarez, Diego (Open Science Journal, 2023)
Manufacturing companies oversee converting raw materials into finished products, characterized by the intervention of machinery and labor force. The article analyzes, through correlation of variables, the relationship between indebtedness and profitability of a group of companies in the Ecuadorian manufacturing sector. The results showed an average debt ratio of 332.70%, which indicates that most of the companies work with money from suppliers or with credits offered by financial institutions. The return on investment shows an average of 113.57%, which indicates that the companies have excellent earnings in terms of what they invest in their economic activity. Correlational analysis showed little or no relationship between return on equity and debt ratio at 21.9%. Likewise, a weak negative relationship between profit margin and indebtedness was evidenced with a -42.4% correlation. In conclusion, the research data indicate that the manufacturing companies have not improved their profitable level by making adequate use of debt.